Strategi Pendidik dalam Menangani Kesulitan Belajar pada Peserta Didik Kelas IV Sekolah Dasar - Fariha Nadhira Lutfia; Fany Riyanawati; Friseza Nayla Zahra; Tamara Noviani Suchi; Zacky Wiryawan Atmaja; Primanita Sholihah Rosmana (Universitas Sebelas Maret, 2025)
This study aims to identify and analyze several strategies that can be applied by educators in overcoming students' learning difficulties in class IV at one of Purwakarta’s elementary schools. The background of this research is based on the challenges that exist for educators in dealing with the diverse characteristics and abilities of students in regular classes. The method used is qualitative. The results showed that students experienced various learning difficulties such as lack of concentration, difficulty understanding the material, and low interest and motivation to learn. To overcome this, educators apply various strategies that can build a more positive learning environment and increase the participation and achievement of student learning outcomes.